Depcition of Kubera - Temples of India Project Team (Jio Institute, 2024)
The dikpala or directional deity Kubera is depicted on the niche of the right-hand side, while the adjoining figure on the left is of Ishana. Vyala is depicted on the subsidiary offset of the temple wall. The image of a directional deity that once adorned the temple wall is now affixed on a late medieval structure on Harsha Hill.